Video Editing: WC126, rev. 7/2021 - Telg, Ricky; Beattie, Peyton (EDIS, 2021)
This 2-page publication about video editing is part of a series about developing effective video production practices. This series also covers video production, scriptwriting, and video equipment and video shot composition. Minor revision by Ricky Telg and Peyton Beattie; published by the UF/IFAS Department of Agricultural Education and Communication.